Studi Etnobotani Kapur Barus (Dryobalanops aromatica Gaertn.) pada Masyarakat Lokal di Kawasan Tahura Lae Kombih, Kecamatan Penanggalan, Subulussalam (Isolation and Analysis of Proteolytic Activity of Local Actinomycetes from Aceh, Indonesia) - Ramadani Sinaga; Essy Harnelly; Saida Rasnovi; Zulia Ananda (Jurnal Bioleuser, 2025)
Lae Kombih Botanical Forest Park is a nature conservation area with the aim of collecting natural and artificial plants and animals that can be utilised for research, science, tourism, and cultural preservation. This study aims to determine the traditional use of camphor (Dryobalanops aromatica Gaertn.) by the local community of Penanggalan District, Subulussalam City. This research used a descriptive survey method through a qualitative-quantitative approach. The results showed five main forms of camphor utilisation by the community, namely as building materials, medicines, natural fragrances for preserving corpses, perfume-making mixtures and food ingredients as building materials, the highest use was found in Sikelang Village (33.33%), followed by Jontor Village (28.21%) and Lae Ikan Village (25.64%). As medicine, the highest utilisation was found in Sikelang Village (25.64%), followed by Lae Ikan Village (23.8%) and Jontor Village (23.08%). For the function as a natural fragrance for preserving corpses, Jontor Village recorded the highest rate (30.77%), while Sikelang and Lae Ikan Villages recorded 23.08% and 20.51% respectively. As a perfume mixture, the highest use was recorded in Lae Ikan Village (17.95%), followed by Jontor Village (12.82%) and Sikelang Village (10.26%). In terms of utilisation as food, Lae Ikan village also showed the highest percentage (12.82%), while Sikelang and Jontor villages recorded 7.69% and 5.13% respectively.